ANALISIS NILAI TAMBAH PENGASAPAN IKAN TAWES DI KABUPATEN LAMONGAN - Wachidatus Sa'adah (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Tawes fish is a freshwater fish that is easy to maintain in ponds and ponds in the Lamongan area and its availability is abundant in the market. However, if it is sold fresh, the price is the cheapest among other types of fish. Therefore, efforts were made to increase the added value of Tawes fish by preserving it using the smoking method. The purpose of this study was to determine the added value of smoking Tawes fish in Lamongan Regency. The method used in this study is a quantitative method, and the sampling is done by purposive sampling, with the calculation of value added analysis using the Hayami method. The final result of the research shows that the added value obtained is Rp. 6.858/kg with the ratio of added value is  24,5%